Construction of multifunctional porcine acellular dermal matrix hydrogel blended with vancomycin for hemorrhage control, antibacterial action, and tissue repair in infected trauma wounds. (September 2021) - Cai, D.; Chen, S.; Wu, B.; Chen, J.; Tao, D.; Li, Z.; Dong, Q.; Zou, Y.; Chen, Y.; Bi, C.; Zu, D.; Lu, L.; et al.
Abstract: Prevention of bacterial infection and reduction of hemorrhage, the primary challenges posed by trauma before hospitalization, are essential steps in prolonging the patient's life until they have been transported to a trauma center. Extracellular matrix (ECM) hydrogel is a promising biocompatible material for accelerating wound closure. However, due to the lack of antibacterial properties, this hydrogel is difficult to be applied to acute contaminated wounds. This study formulates an injectable dermal extracellular matrix hydrogel (porcine acellular dermal matrix (ADM)) as a scaffold for skin defect repair. The hydrogel combines vancomycin, an antimicrobial agent for inducing hemostasis, expediting antimicrobial activity, and promoting tissue repair. The hydrogel possesses a porous structure beneficial for the adsorption of vancomycin. The antimicrobial agent can be timely released from the hydrogel within an hour, which is less than the time taken by bacteria to infest an injury, with a cumulative release rate of approximately 80%, and thus enables a relatively fast bactericidal effect. The cytotoxicity investigation demonstrates the biocompatibility of the ADM hydrogel. Dynamic coagulation experiments reveal accelerated blood coagulation by the hydrogel. In vivo antibacterial and hemostatic experiments on a rat model indicate the healing of infected tissue and effective control of hemorrhaging by the hydrogel. Therefore, the vancomycin-loaded ADM hydrogel will be a viable biomaterial for controlling hemorrhage and preventing bacterial infections in trauma patients. Graphical abstract: Image 1